The misti identity in the Andes: notes for a debate - Plasencia Soto, Rommel Humberto (2015)
The present communication shows the social and ideological, bases that have contributed to what they call misti thought, i.e., the non-indigenous view of the landscape, culture and Andean society. Our hypothesis is that although their status as landowners or being related to them, provided them elements to explain the culture of the peasants, it represented a severe restriction because their social position presented them from developing an empathy toward their subjects narrated and an alternative for change from below.